High-performance soybean protein / glucan graft, preparation method thereof and application of high-performance soybean protein / glucan graft in stabilizing anthocyanin

Through ultrasonic induction combining low-temperature and high-temperature humid and heat segmented reactions, the problems of poor soy protein isolate and difficult to control glycosylation reactions are solved, and the efficient preparation of soy protein/glucan grafts are achieved, which improves its surface function and the stability of anthocyanins.

CN119529291APending Publication Date: 2025-02-28CHENGDU NORMAL UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411775648.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-05
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The molecular weight of soy protein isolate is large, resulting in poor solubility, limiting its use in specific food applications. At the same time, the glycosylation reaction conditions are difficult to control, which easily produces harmful browning compounds, limiting its industrial applications.

Method used

Ultrasonic-induced cavitation effect is used to combine low-temperature, humidity and heat and high-temperature, humidity and heat segmentation reactions. Through the combined use of ultrasonic technology, high-temperature, humidity and heat reactions and circulation reactions, the degree of browning is controlled and the grafting efficiency and surface functional characteristics of soy protein/glucan grafts are improved.

Benefits of technology

The grafting efficiency of soy protein/glucan grafts is significantly improved, the browning index is reduced, its surface function and anthocyanin packaging efficiency are enhanced, and the stability and bioavailability of anthocyanins are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119529291A_ABST
    Figure CN119529291A_ABST
Patent Text Reader

Abstract

The invention provides a high-performance soybean protein / glucan graft as well as a preparation method and application of the high-performance soybean protein / glucan graft in stabilizing anthocyanin, and belongs to the technical field of plant protein modification processing. Comprising the following steps: (1) dissolving soybean protein isolate and glucan with ultrapure water, adjusting the pH value to be neutral, and carrying out a primary reaction to obtain a mixed solution 1; (2) sequentially carrying out low-temperature damp-heat reaction and ultrasonic-assisted high-temperature damp-heat reaction on the mixed solution 1, continuously circulating for multiple times, and terminating the circulating reaction to obtain a mixed solution 2; and (3) adjusting the pH value of the mixed solution 2 to be acidic, carrying out solid-liquid separation, taking supernate, and drying to obtain the soybean protein / glucan graft. According to the method, the high-performance soybean protein / glucan graft can be synthesized by utilizing a method of ultrasonic synergistic damp-heat circulation continuous reaction, the browning degree is controlled, the Maillard reaction kinetics is enhanced, and the surface functional characteristics and anthocyanin packaging efficiency are enhanced, so that the method has a wide application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of plant protein modification and processing, and particularly relates to a high-performance soybean protein / glucan graft and a preparation method thereof and application thereof in stabilizing anthocyanins. Background Art

[0002] With the environmental challenges brought by the production of animal proteins and the increasing public awareness of the health benefits of plant proteins, plant-based protein foods have attracted widespread attention from scientists around the world. Among various plant proteins, soy protein isolate (SPI) is a cheap, low-cost, high-efficiency, high-quality protein resource with similar nutrition to animal proteins. It has nutritional advantages, processing characteristics advantages (hydration properties, surface properties and fluid dynamics properties) and application potential of microcapsules and nanocarriers, and is a key component for food industry applications. However, the large molecular weight of the globulin contained in soy protein isolate will hinder its surface properties, resulting in poor solubility, resulting in limited emulsification, foaming and nutrient delivery capabilities, thereby limiting its use in specific food applications. Previous studies have shown that glycosylation is a non-enzymatic browning reaction of reducing sugars interacting with protein amino groups, which can enhance the functional properties of the protein surface when interacting with polysaccharides. However, the preparation of SPI grafts remains challenging. First, the glycosylation reaction conditions are difficult to accurately control, and the degree of browning increases with the increase in the degree of grafting. Compared with the early stages of the glycation reaction, the middle and late stages are more sensitive to changes in reaction conditions and tend to produce more advanced glycation end products (AGEs) and other harmful browning compounds. These compounds increase cytotoxicity and are associated with chronic diseases, which is a key factor limiting its industrial application. Secondly, SPI is usually compactly spherical, with a large number of chemically reactive amino acids buried inside, which brings difficulties to the grafting reaction. Therefore, new technologies are needed to control the degree of browning and improve the kinetics of the Maillard reaction, thereby improving the surface functional properties and nutrient encapsulation efficiency of SPI grafts.

[0003] In order to control browning and enhance the kinetics of glycosylation reaction, the use of suitable polysaccharides for glycosylation reaction is considered to be one of the safest and most effective methods. Glucan is a linear polysaccharide connected by α-(1→6) glycosidic bonds. It has the inherent advantages of reducing, neutral charge, low viscosity and no gelation. It is often used as a sugar source for glycosylation reaction. It can avoid the formation of electrostatic complexes of proteins, reduce the complexity of Maillard reaction, increase steric hindrance, improve protein functional properties and encapsulation performance, and is widely used in protein modification. Studies have shown that the maximum grafting efficiency of soy protein isolate / dextran (SPI / D) grafts prepared by glycosylation dry heating technology is about 40%. However, the long reaction time of this technology is not conducive to industrial-scale application. He et al. developed a two-step wet-heat grafting technology, which significantly shortened the reaction time and promoted the synthesis of SPI / D grafts through continuous cyclic reactions within a high-concentration polysaccharide matrix. This method effectively alleviated the browning problem and improved the efficiency of soy protein grafting. However, the final grafting degree is still low, only 42% (Wanying H, Liang T, Shanshan Z, et al. A novel method to prepare protein-polysaccharide conjugates with high grafting and low browning: Application in encapsulating curcumin [J]. LWT, 2021, 145). The grafting degree is crucial to the surface functionality and nutrient encapsulation efficiency of protein-polysaccharide grafts. Therefore, it is necessary to adopt innovative methods to improve the grafting efficiency of SPI / D grafts while controlling browning.

[0004] The ultrasound-induced cavitation effect can promote the interaction between proteins and polysaccharides and improve the grafting efficiency of proteins and polysaccharides. This process will lead to the elongation and loosening of the protein structure, thereby enhancing the surface function and functional factor encapsulation efficiency of the protein-polysaccharide graft. In recent years, researchers have mainly used ultrasound-assisted glycosylation to modify soy protein for hydrophobic delivery research. However, research on the delivery of hydrophilic functional factors is still limited. As a typical representative of hydrophilic functional factors, anthocyanins (ANs) have excellent antioxidant capacity and can improve human health by affecting the structure of intestinal microbial communities and regulating uric acid metabolism. However, the poor stability and low bioavailability of this antioxidant limit the full play of its health benefits. Summary of the invention

[0005] The object of the present invention is to provide a soybean protein / glucan grafted product with a high grafting rate, capable of loading antioxidant active substances and improving the stability of the antioxidant active substances.

[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0007] The present invention provides a method for preparing a high-performance soybean protein / glucan graft, comprising the following steps:

[0008] (1) dissolving soy protein isolate and glucan in ultrapure water, adjusting the pH to neutral, and performing a preliminary reaction to obtain a mixed solution 1;

[0009] (2) subjecting the mixed solution 1 to a low-temperature wet heat reaction and an ultrasound-assisted high-temperature wet heat reaction in sequence, and after multiple cycles, terminating the cycle reaction to obtain a mixed solution 2;

[0010] (3) adjusting the pH of the mixed solution 2 to acidic, separating the solid and the liquid, and drying the supernatant to obtain a soy protein / glucan graft;

[0011] The low temperature in the low-temperature wet heat reaction in step (2) is less than 65°C; the high temperature in the ultrasound-synergistic high-temperature wet heat reaction is greater than 80°C.

[0012] Preferably, the final concentration of the soy protein isolate in ultrapure water in step (1) is 1.2-1.6% (w / v);

[0013] The final concentration of the dextran in ultrapure water is 0.5-1.0% (w / v);

[0014] The molecular weight of the dextran is 35-45 KDa.

[0015] Preferably, the low-temperature wet heat reaction in step (2) is carried out for 10 to 30 minutes at a temperature of 55 to 65° C., and low-speed stirring is required at a speed of 5 to 120 rpm.

[0016] Preferably, the ultrasound-assisted high-temperature wet heat reaction in step (2) is as follows: after the low-temperature wet heat reaction is completed, the temperature is raised to 80-90° C., and ultrasound-assisted reaction is performed at a power of 200-500w for 5-30min;

[0017] The number of consecutive cycles is 2 to 7 times.

[0018] Preferably, the pH value after adjustment in step (3) is 4.0 to 5.0;

[0019] The conditions for the solid-liquid separation are: 5000-10000 rpm, centrifugation for 20-30 min.

[0020] The invention provides a soybean protein / glucan graft prepared by the preparation method.

[0021] The present invention also provides the use of the soybean protein / glucan graft in stabilizing anthocyanin.

[0022] The method for stabilizing anthocyanins comprises: dissolving the soy protein / glucan graft and anthocyanin respectively with water to obtain a soy protein / glucan graft solution and anthocyanin solution, mixing them, and then homogenizing them at 5000-10000 rpm for 2-8 minutes, separating the solid and the liquid, taking the supernatant and drying it to obtain nanoparticles of the soy protein / glucan graft loaded with anthocyanin.

[0023] Preferably, the concentration of the soy protein / glucan graft in the soy protein / glucan graft solution is 5 to 10 mg / mL;

[0024] The final concentration of anthocyanins in the anthocyanin solution is 5 to 10 mg / mL;

[0025] The volume ratio of the soy protein / glucan graft solution to the anthocyanin solution is 1 to 2:1;

[0026] The solid-liquid separation is performed under the conditions of 5000-10000 rpm and centrifugation for 5-20 min.

[0027] Beneficial Effects

[0028] (1) The present invention adopts low-temperature wet heat and high-temperature wet heat segmented reaction in the wet heat cycle reaction process, and combines the use of ultrasonic technology, high-temperature wet heat reaction, and cyclic reaction, which not only reduces the time of high-temperature wet heat reaction, but also significantly improves the SPI / D reaction efficiency. In particular, in the 7th cycle, the grafting degree reaches a maximum of 65.92±3.69%, which is more than 20% higher than the prior art, while the maximum value of the browning index is only 14.93±0.14, which can maximize the grafting efficiency while successfully reducing browning;

[0029] (2) In the process of wet heat cycle reaction, the present invention uses ultrasonic technology, high temperature wet heat reaction and cycle reaction in combination to increase the β-folding content of SPI, reduce the β-turn and random coil content, enhance the covalent binding of SPI and dextran, reduce the hydrophobicity of SPI / D grafts, and promote the tightening of the secondary structure of soy protein isolate molecules and the unfolding of the tertiary structure;

[0030] (3) In the process of wet heat cycle reaction, the present invention can enhance the solubility of SPI / D by combining ultrasonic technology, high temperature wet heat reaction and cycle reaction. The solubility reaches a maximum of 57.36±2.31% at SPI / D-7. The emulsification of SPI / D grafted products is increased, and the maximum value of EAI is 14.57±1.66m 2 / g, the maximum value of ESI is 35.27±2.9min; the present invention finds that the mechanical effect of ultrasound can improve the surface activity of SPI / D grafts, ensure the foaming capacity (FC) and foam stability (FS) of the grafts, and the maximum values ​​are 20.18±2.7% and 31.62±4.19% respectively; at the same time, it is also found that the combined use of ultrasound technology, high temperature and wet heat reaction, and cyclic reaction can significantly improve the antioxidant activity and free radical scavenging ability of SPI / D;

[0031] (4) The grafted product prepared by the present invention can be used to load antioxidant active substances (such as anthocyanins), and the size of the obtained nanoparticles and the absolute value of the Zeta potential increase with the increase of the continuous reaction of ultrasound-assisted moist heat cycle;

[0032] (5) Under the conditions of the combined use of ultrasound technology, high temperature and humidity reaction, and cyclic reaction, the nanoparticles (SPI / D / ANs) prepared in the seventh cycle can significantly improve the thermal stability, storage stability, light stability and tolerance to simulated gastrointestinal digestion of anthocyanins, as well as the resistance to hydrogen peroxide and Fe 3+ The degradation ability of anthocyanins can improve the stability and bioavailability of anthocyanins, which helps to further exert their health benefits.

[0033] (6) The present invention performs low-temperature heat treatment on soy protein isolate (final concentration 1.4%, w / v) and glucan (molecular weight 40KDa, final concentration 0.7%, w / v) at a mass ratio of 2:1 at a relatively low temperature (lower than 65°C) and relatively slow stirring conditions to ensure complete dispersion and mixing of soy protein and glucan biomacromolecules (forming a small amount of protein polymers), and to initialize the grafting of soy protein and glucan, and then heat the mixture to a temperature greater than 80°C for high-temperature heat treatment, while simultaneously performing 325W ultrasonic treatment for 10 minutes to improve grafting efficiency and prevent excessive browning. This process will intensify the effective interaction between protein and polysaccharide biomolecules and reduce excessive aggregation of proteins.

[0034] In summary, the present invention utilizes ultrasound-assisted moist-heat cycle continuous reaction method to synthesize high-performance SPI / D grafted materials to control the degree of browning and enhance the kinetics of Maillard reaction, thereby enhancing its surface function and anthocyanin encapsulation efficiency, improving the stability and bioavailability of anthocyanins, giving soy protein new functional activity, and developing high-value soy protein ingredients, which have broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 Flow chart for the preparation of SPI / D grafted products.

[0036] Figure 2This is the effect of ultrasound-assisted moist-heat cycle continuous reaction on the grafting degree of SPI / D grafted products.

[0037] Figure 3 The effect of ultrasound-assisted moist-heat cycle continuous reaction on the browning degree of SPI / D grafted materials.

[0038] Figure 4 The effect of ultrasound-assisted moist-heat cycle continuous reaction on the browning index of SPI / D grafted materials.

[0039] Figure 5 is the UV-visible absorption spectrum of SPI / D grafted product.

[0040] Figure 6 Fourier transform infrared spectrum of SPI / D grafted product.

[0041] Figure 7 is the secondary structure content of SPI / D grafted product.

[0042] Figure 8 is the fluorescence spectrum of SPI / D grafted product.

[0043] Fig. 9 Surface hydrophobicity of SPI / D grafted polymer.

[0044] Fig.10 This is the effect of ultrasound-assisted moist-heat cycle continuous reaction on the solubility of SPI / D grafted compounds.

[0045] Fig.11 This is the effect of ultrasound-assisted moist-heat cycle continuous reaction on the emulsification of SPI / D grafted materials.

[0046] Fig.12 This is the effect of ultrasound-assisted moist-heat cycle continuous reaction on the foaming properties of SPI / D grafted materials.

[0047] Fig.13 This is the effect of ultrasound-assisted moist-heat cycle continuous reaction on the DPPH radical scavenging ability and ABTS radical scavenging ability of SPI / D grafted compounds.

[0048] Fig.14 This study investigates the effects of ultrasound-assisted wet-heat cycle continuous reaction on the hydroxyl radical scavenging ability and iron ion reducing ability of SPI / D grafts.

[0049] Fig.15 UV-visible absorption spectrum of SPI / D / ANs nanoparticles.

[0050] Fig.16 Fourier transform infrared spectrum of SPI / D / ANs nanoparticles.

[0051] Fig.17This is the intrinsic fluorescence spectrum of SPI / D / ANs nanoparticles.

[0052] Fig.18 Synchronous fluorescence spectrum of SPI / D / ANs nanoparticles when Δλ=15.

[0053] Fig.19 Synchronous fluorescence spectrum of SPI / D / ANs nanoparticles when Δλ=60nm.

[0054] Fig. 20 Thermal stability of SPI / D / ANs nanoparticles.

[0055] Fig.21 The storage stability of SPI / D / ANs nanoparticles.

[0056] Fig. 22 The photostability of SPI / D / ANs nanoparticles.

[0057] Fig.23 The oxidative stability of SPI / D / ANs nanoparticles.

[0058] Fig.24 Fe of SPI / D / ANs nanoparticles 3+ Ionic stability.

[0059] Fig.25 In vitro simulated digestion stability characteristics of SPI / D / ANs nanoparticles. DETAILED DESCRIPTION

[0060] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0061] Example 1: Preparation of SPI / D grafted products

[0062] (1) ultrapure water, soy protein isolate (final concentration 1.4%, w / v) and dextran (molecular weight 40 KDa, final concentration 0.7%, w / v) were mixed. The solution was adjusted to a pH of 7.0 using 0.1 M hydrochloric acid and 0.1 M sodium hydroxide, and stirred continuously at 30 rpm for 2 h at room temperature (25° C.) to obtain a mixed solution 1;

[0063] (2) The heating temperature of the mixed solution 1 was adjusted to 60°C, and the mixture was stirred at a low speed of 80 rpm for 20 min, then the temperature was raised to 83°C, and ultrasonic treatment was performed at 325 W for 10 min to obtain a mixed solution 2;

[0064] (3) The step (2) was continuously cycled for 7 times to obtain 1 to 7 different cycle-treated soy protein isolate-glucan grafts (SPI / Dn, n represents the number of cycle reactions). The cycle reaction was terminated by cooling in an ice water bath to obtain a mixed solution 3;

[0065] (4) The pH value of the mixed solution 3 was adjusted to 4.5 using 1 M hydrochloric acid to remove unreacted soy protein isolate, followed by centrifugation at 5000 rpm for 20 min. The supernatant was freeze-dried (pre-freezing temperature -80°C, pre-freezing time 10 h; vacuum freeze-drying temperature -55°C, vacuum freeze-drying time 42 h, vacuum degree 5 Pa) to obtain a soy protein / dextran (SPI / D) graft, which was stored in a -20°C refrigerator (preparation flow chart as shown in FIG. 1 ). Figure 1 shown).

[0066] Example 2: Preparation of SPI / D grafted anthocyanin nanoparticles

[0067] (1) The soy protein / dextran (SPI / Dn) graft and purple sweet potato anthocyanin (ANs) powder prepared in Example 1 were dissolved in ultrapure water to prepare SPI / Dn solution and purple sweet potato anthocyanin solution with a concentration of 5 mg / mL, and the mixture was mixed in a volume ratio of 1:1. The mixture was homogenized at a speed of 8000 rpm for 3 minutes, and then centrifuged at a speed of 8000 rpm for 10 minutes to separate the nanoparticles from the insoluble and unencapsulated ANs. The supernatant was taken and freeze-dried to obtain nanoparticles of soy protein / dextran graft loaded with anthocyanins.

[0068] Specifically, the present invention provides the following experiments and principles to explain the present invention:

[0069] The experimental groups were 7 groups with 1 to 7 different cycles of soy protein isolate-dextran grafts (SPI / Dn, n represents the number of cycles).

[0070] The control groups included 2 groups: NSPI / D-7 group (treated with 7 cycles but without ultrasound treatment) and SPI / 7 group (treated with 7 cycles of ultrasound-assisted continuous cycle treatment without adding dextran).

[0071] Test Example 1 Detection of Grafting Degree (DG) and Browning Intensity

[0072] Detection method:

[0073] Evaluation of degree of grafting (DG) using o-phthalaldehyde (OPA) assay

[0074] The calculation formula of DG is DG%=(A 0 -A t ) / A0 ×100%(1),

[0075] Among them A t is the absorbance of the grafted product, A 0 is the absorbance of the protein and sugar mixture.

[0076] Determination of color difference and browning index: After the sample is evenly ground, the color parameters (L*, a*, b*) are evaluated using a colorimeter calibrated with a standard black and white plate. Each sample is measured five times. The calculation formula of the browning index (BI) is as follows:

[0077] X=(a*+1.75L*) / (5.645L*+a*-3.012b*) (2);

[0078] BI=(100×(x-0.31)) / 0.172(3);

[0079] Browning intensity

[0080] The absorbance was measured at 294 nm and 420 nm using a spectrophotometer and expressed as A 294 and A 420 The Stanic-Vucinic method was used to evaluate the intermediate products of the primary stage and the melanoidin products of the final stage. 294 and A 420 They correspond to the absorbance values ​​at the primary and advanced stages of the grafting reaction, respectively.

[0081] Test results: DG and browning intensity of SPI / D grafts

[0082] like Figure 2 As shown in the figure, the DG in the SPI / D graft increases with the increase of the glycosylation reaction cycle, and the DG of SPI / D-7 reaches a peak at 65.92±3.69%. This increase is due to the fact that the glycosylation reaction and thermal processing change the conformation of SPI, exposing more free amino groups, which increases the contact probability between the two and promotes the grafting reaction. Compared with NSPI / D-7 and the research report of He et al., the DG of SPI / D-7 increased significantly by 21.3% and 23.92%, respectively. This shows that ultrasound synergistic wet heat cycle continuous reaction can effectively increase DG.

[0083] like Figure 3 As shown in the figure, with the increase of cycle number, the absorbance of SPI / D grafted product at 294nm wavelength gradually increased from 0.138 to 0.271. This confirms the saccharification reaction between SPI and dextran and indicates that the reaction is the early stage of saccharification reaction to generate Maillard product. 294, the absorbance change of SPI / D-7 at 420nm wavelength was the smallest, and the maximum value was 0.17±0.006. In the first seven cycles, the A 420 The values ​​were all kept below 0.18. This indicates that the browning degree was low and the glycosylation reaction could be effectively controlled at the initial stage by preventing the synthesis of high molecular weight melanoidins and the production of brown chromophores.

[0084] Figure 4 It was shown that the browning index of the SPI / D graft increased as the cyclic reaction proceeded, reaching a maximum value of 14.93±0.14 at the seventh cycle. The browning rate seemed to stabilize after the sixth cycle. This plateau may be due to the increased covalent binding of glucan to protein, which caused a steric hindrance to further grafting and pigmentation. As the grafting reaction proceeds, the glucan molecules covalently bound to the protein surface may increase the steric resistance, thereby slowing down the browning rate. Nevertheless, the browning index of SPI / D-7 is still much lower than the browning index of whey protein isolate-dextran grafting reported by Liu et al. (about 55) (Qian L, Heping C, Bertrand M, et al. Whey protein isolate-dextran conjugates: Decisive role of glycation time dependent conjugation degree insize control and stability improvement of colloidal nanoparticles[J]. LWT, 2021, 148), which shows that our method successfully reduced browning while maximizing the grafting efficiency. The browning index of ultrasonically treated SPI / D-7 increased by 1.64 times compared with that of NSPI / D-7. This finding further confirmed that the combination of ultrasonic technology and high temperature and humidity reaction had a positive effect on the effective binding of glucan and SPI during the humidity and heat cycle reaction.

[0085] Experimental Example 2: Effect of ultrasound-assisted wet-heat cycle continuous reaction on the structure of SPI / D grafted products

[0086] 1. Detection method:

[0087] UV-Vis absorption spectrum

[0088] The SPI / D graft was diluted to a protein concentration of 1 mg / mL in PBS buffer (0.01 M, pH 7.0) and then subjected to UV-Vis spectroscopy analysis. The absorbance was measured in the range of 200-450 nm.

[0089] Fourier transform infrared spectroscopy

[0090] The sample was mixed with KBr powder in a weight ratio of 1:100 to prepare a KBr disk. The parameters of Fourier transform infrared spectroscopy (FTIR) were 400-4000cm -1 , resolution 8cm -1 , the scanning frequency is 16, and the scanning temperature is 25℃.

[0091] Intrinsic fluorescence spectroscopy

[0092] Using F-380 spectrophotometer, the sample was diluted to 0.2 mg / mL with deionized water. The emission wavelength was 290 to 450 nm, the excitation wavelength was 280 nm, the voltage was 460 V, the slit width was 5 nm, and the scanning speed was 1200 nm / min.

[0093] Surface hydrophobicity

[0094] The surface hydrophobicity (H) was determined by ANS fluorescence method. 0 ), the concentration of protein samples in 10mM phosphate buffer (pH7.0) was adjusted to 0.005 to 0.2mg / mL, and the concentration of ANS in the same buffer was 8mM. After treating each sample with 40μLANS, incubate at 25℃ in the dark for 15 minutes, and then measure the fluorescence emission in the wavelength range of 360 to 700nm. The excitation wavelength was 390nm, the slit width was 5.0nm, and the voltage was 400V.

[0095] 2. Test results:

[0096] UV-Vis absorption spectroscopy analysis

[0097] like Figure 5 As shown in the figure, the maximum absorption wavelength decreases with the increase of the number of cycles, which indicates that the addition of dextran may shelter the tryptophan (Trp) and tyrosine (Tyr) residues inside the protein molecule to some extent, thus providing a protection mechanism against SPI destruction. In addition, the unfolded protein structure may further glycosylate more aromatic residues, thereby reducing UV absorption. With the increase of cycles, the maximum absorption peak shifted slightly from 285 nm to 287 nm, indicating a closer interaction between SPI and dextran. Compared with NSPI / D-7, the maximum absorption peak of SPI / D-7 is lower. Sensitive functional groups will be oxidized by long-term exposure to high-intensity ultraviolet light, thereby reducing the UV absorbance of the sample. Therefore, aromatic amino acids, especially tryptophan (Trp), tyrosine (Tyr) and phenylalanine (Phe), are easily oxidized under the cavitation effect of ultrasonic impact, thereby reducing the absorbance.

[0098] Fourier Transform Infrared Spectroscopy

[0099] Figure 6 It shows that when the number of continuous reactions of ultrasound-assisted wet-heat cycles increases, the absorption of the amide band of the SPI / D grafted product decreases. This indicates that -NH 2 The groups are largely consumed for covalent bonding, thus reducing NH bending and CN stretching vibrations. As the ultrasonic-assisted wet-heat cycle reaction proceeds, the 3110 cm -1 and 1090cm -1 The vibration intensity of the peaks near 1014cm gradually increased and reached the maximum intensity after the seventh cycle. This indicates that with the increase in the number of cycles, the number of free hydroxyl groups and sugar rings in the sample gradually increased, indicating a high degree of saccharification. Compared with SPI / 7, SPI / D-7 has a -1 A new peak appears near 700-950cm. The appearance of this new peak is related to the stretching vibration of the COC glycosidic bond. -1 Several peaks are formed in the range, especially at 765 and 915 cm -1 At 1150cm -1 New peaks also appeared nearby. These are mainly related to the synthesis of intermediates in the glycosylation process, including Schiff bases and pyrazines. Compared with NSPI / D-7, the intensity of amide I to III bands in SPI / D-7 decreased, which proves that the degree of glycosylation is higher, which is consistent with the grafting results.

[0100] Figure 7 The results showed that the β-sheet structure dominated the SPI / D grafts. With the increase of the number of continuous reactions of ultrasound-assisted moist-heat cycles, the content of β-sheets fluctuated, initially increasing, then decreasing, and finally increasing again. In contrast, the content of β-turns showed a trend of first decreasing and then increasing, while the content of α-helices decreased significantly, which may be due to the partial unfolding of α-helices caused by ultrasonic cavitation. This increase in β-sheets and reduction in α-helices enhanced the flexibility of the protein. Compared with SPI / 7 and NSPI / D-7, SPI / D-7 showed higher β-sheets and lower β-turn and random coil contents, indicating that the protein secondary structure was more ordered and compact.

[0101] Fluorescence spectroscopy analysis

[0102] Figure 8It was shown that with the increase in the number of continuous reactions of ultrasound-synergistic wet heat cycles, the fluorescence spectrum shifted to the blue region and the intensity decreased, indicating that glycosylation caused the peptide chain to unfold and Tyr and Trp residues were exposed to a more hydrophobic environment, indicating that the tertiary structure of SPI became more relaxed. This change in the microenvironment weakened the absorption of the chromophore. The covalent connection between dextran and SPI also shielded the fluorescence signal. The higher the degree of glycosylation (DG), the lower the fluorescence intensity. In this study, the grafted dextran effectively prevented the exposure of hydrophobic residues, which was beneficial to inhibit the extensive aggregation of proteins during heating. Compared with SPI / 7 and NSPI / D-7, the fluorescence spectrum of SPI / D-7 showed a blue shift and a decrease in fluorescence intensity. This indicates that the glycation reaction changed the spatial structure of SPI and Trp participated in the glycosylation reaction. At the same time, the synergistic effect of ultrasound increased the number of attached dextran molecules, thereby masking the emission intensity of the protein itself. In addition, there may be hydrophobic interactions between Tyr and Trp, which may form a hydrophobic environment inside the protein, resulting in a blue shift in the maximum emission wavelength (λmax).

[0103] Surface hydrophobicity

[0104] Fig. 9 It shows that with the increase of the number of continuous reactions of ultrasound-assisted moist heat cycle, H 0 The decrease may be due to the inward migration of hydrophobic groups or the adhesion of dextran to SPI, which shields these groups from contact with ANS. This change reduces hydrophobic interactions and thus inhibits protein aggregation during heating. The hydrophobicity of SPI / D-7 is significantly lower than that of NSPI / D-7 (p<0.05), which indicates that ultrasonic treatment enhances the covalent binding of SPI to dextran, introduces hydrophilic hydroxyl groups, breaks the hydrophilic-hydrophobic balance, and reduces the hydrophobicity of the graft.

[0105] Experimental Example 3: Effects of ultrasound-assisted wet-heat cycle continuous reaction on the functional properties and antioxidant capacity of SPI / D grafts

[0106] 1. Detection method:

[0107] Solubility

[0108] A protein standard curve (y = 0.0089x + 0.0605, R 2 =0.9983). After weighing, dissolving and centrifuging the sample, 1 mL of the supernatant was mixed with 5 mL of Brilliant Blue G-250 reagent. Deionized water was used as a blank control. After standing in the dark for three minutes, the absorbance at a wavelength of 595 nm was measured. The solubility was determined using the following formula:

[0109] Solubility (%) = C s / C 0 ×100(4)

[0110] The protein concentration in the supernatant is expressed as C S The total protein concentration in the solution is expressed as C 0 express.

[0111] Emulsifying properties

[0112] A 0.1% (w / v) sample solution was added to a 0.2 mol / L PBS buffer at a pH of 7.0. Then, 12 mL of the solution was mixed with 4 mL of corn oil in a 50 mL EP tube and homogenized at 10,000 rpm and 25°C for 1 minute. Samples were collected at 0 and 10 minutes after homogenization, diluted 50 times with a 0.1% (w / v) SDS solution at a pH of 7.0, and their absorbance at a wavelength of 500 nm was compared with the SDS blank value. The emulsification activity index (EAI) and emulsification stability index (ESI) were calculated according to the following formula:

[0113] EAI(m 2 / g) = (2 × 2.303 × A 0 ×N) / (C×L×θ×10000)(5)

[0114] ESI(min)=(A 0 ×t) / (A 0 -A t )(6)

[0115] Among them, A 0 and A t represents the absorbance of the emulsion at 0 minutes and 10 minutes respectively. The concentration of SPI is C (g / mL). L is the optical path length of the cuvette (1 cm). t is the time interval (min), and θ is the volume percentage of the oil phase in the emulsion medium.

[0116] Foaming properties

[0117] The foaming capacity (FC) and stability (FS) of the SPI / D grafts were evaluated using an ESFSL-1 homogenizer. 20 ml of a 1% w / v sample solution was homogenized at 10,000 rpm for 1 min. The FC and FS were calculated using the following formula:

[0118] FC(%)=(V 0 -V i ) / V i ×100(7)

[0119] FS(%)=(V 30 -V i ) / (V 0 -V i )×100(8)

[0120] In this formula, V i Indicates the liquid level before homogenization, V 0 Indicates the liquid level after 0 minutes of homogenization, V 30 Indicates the liquid level after standing for 30 minutes.

[0121] Antioxidant Capacity

[0122] The ability of SPI / D grafts to scavenge DPPH (2,2-diphenyl-1-picrylhydrazyl) free radicals (DPPH·) was used to evaluate their antioxidant potential, ABTS free radicals (ABTS +. ) and hydroxyl radical (·OH), and the results are expressed as vitamin C (Vc) equivalents. The standard curve equations for these tests are: DPPH·y=175.32x+0.0693(R 2 =0.9977), ABTS +. y=160.88x+0.3023(R 2 =0.976),.OH y=0.9648x-0.265(R 2 =0.9936). In addition, the iron ion reducing power (FRAP) of the grafted product was determined, and the results were expressed in micromolar Fe 2+ FRAP values ​​(μM Fe 2+ ) is represented by the equation of the standard curve for FRAP analysis: y = 0.9648x - 0.265 (R 2 =0.9936).

[0123] 2. Results:

[0124] Fig.10 The results showed that the solubility of SPI / D grafts increased with the increase of the number of consecutive reactions under ultrasound-assisted moist heat cycles, reaching a peak of 57.36±2.31% at SPI / D-7. This improvement may be due to (1) the introduction of hydrophilic hydroxyl groups into the grafts, which reduced the hydrophobicity of SPI through covalent glucan linkage; (2) the steric structure of glucan hindered the aggregation of SPI molecules and improved the interaction between water and protein, which was consistent with the observed reduction in hydrophobicity. The solubility of SPI / D-7 was significantly higher than that of NSPI / D-7 (p<0.05), which may be attributed to (1) the ultrasonic cavitation effect decomposed the aggregates and improved the solubility; (2) the mechanical force and cavitation force destroyed the hydrogen bonds and hydrophobic bonds, resulting in partial protein disintegration or hydrolysis, increasing their accessibility to hydrophilic molecules; (3) the ultrasonic treatment exposed more positively charged groups, improving the solubility and electrostatic repulsion. The increased solubility of SPI / D-7 compared with SPI / 7 further confirmed the beneficial effects of ultrasound and glycosylation synergistically on the solubility of SPI.

[0125] Fig.11 The results showed that the EAI and ESI of SPI / D grafts reached their peak values ​​at SPI / D-4, with the maximum values ​​being 14.57±1.66m2 / g and 35.27±2.9min, respectively. The glycosylation reaction increased the polysaccharide content in the grafts, thickened the protein film at the oil-water interface, and increased the oil droplet repulsion, which was the reason for the initial increase in EAI and ESI. However, further glycosylation would reduce the surface hydrophobicity of SPI, destroy the balance of hydrophilic and hydrophobic properties of the protein, impair its interfacial adsorption, and thus reduce the emulsification efficiency. The EAI and ESI of SPI / D-7 were significantly lower than those of NSPI / D-7 and SPI / 7 (p<0.05), indicating that prolonged ultrasound and glycosylation would lead to protein reaggregation, reducing the emulsification performance and emulsion stability.

[0126] like Fig.12 As shown in the figure, the foaming capacity (FC) and foam stability (FS) of SPI / D grafts increased with the increase of ultrasound-synergistic wet-heat cycle continuous reaction; the two values ​​of SPI / D-7 reached peak values ​​of 20.18±2.7% and 31.62±4.19%, respectively. The hydrophilic sugar groups improved the solubility and diffusion rate of SPI at the water-air interface. With the increase of reaction, grafting more sugars on SPI can further improve FC and FS. The mechanical effect of ultrasound will expose the hydrophobic groups of SPI, promote molecular migration and interfacial adsorption, and increase surface activity. Compared with NSPI / D-7 and SPI / 7, the FC and FS of SPI / D-7 were significantly improved (p<0.05). The introduction of polysaccharides increased the system viscosity, thickened the foam film, reduced drainage, and thus improved the foam stability.

[0127] Fig.13 and 14 Display, ABTS of SPI / D + The scavenging abilities of · and ·OH increased with the increase in the number of consecutive reactions of ultrasound-assisted moist-heat cycles, reaching a peak at SPI / D-7, while the scavenging abilities of DPPH· peaked at SPI / D-6 and FRAP peaked at SPI / D-4, showing a trend of first increasing and then decreasing. The enhancement of free radical scavenging ability is attributed to the exposure of buried protein residues during glycosylation, which increases the hydrogen donor capacity, and the increase in the degree of polysaccharide grafting, which provides more hydrogen donors. The difference in scavenging ability between free radicals is due to their hydrophilicity / hydrophobicity; DPPH· is hydrophobic, while ABTS· is hydrophobic. + · and ·OH are hydrophilic, resulting in different interactions with the SPI / D grafts. In addition, the study showed that the reduced iron reducing power may be due to the reduced electron and hydrogen energy supply capacity of the SPI / D grafts after the glycosylation reaction. Compared with NSPI / D-7, the antioxidant activity (DPPH·, ABTS+ Ultrasound may generate more hydroxyl groups and atomic donors, thus improving its ability to scavenge free radicals.

[0128] Experimental Example 4: Properties of SPI / D / ANs Nanoparticles

[0129] Nanoparticles of soy protein / dextran grafts (SPI / D / ANs) loaded with anthocyanins of different cycles prepared in Example 2 were used as test groups, named SPI / D / ANs-n (n=number of cycles), with a total of 7 groups. Free ANs solution was used as a control for dynamic light scattering analysis (DLS), and the analysis method was as follows: dynamic light scattering was performed using Zetasizer Nano ZSE to determine the particle size, polydispersity index (PDI) and zeta potential of SPI / D / ANs. Each 1 mg / mL sample was equilibrated at 25°C for 60 seconds, and then the light scattering at 633nm and 173° was measured at room temperature (298K), with 10 seconds for every 11 scans. For accuracy, this process was repeated three times, and the results are shown in Table 1.

[0130] Table 1 Average particle size, polydispersity index and zeta potential of SPI / D / ANs nanoparticles

[0131] sample Particle size / nm Polydispersity Index PDI ζ-potential / mV SPI / D / ANs-1 <![CDATA[322.73±4.63 d ]]> <![CDATA[0.517±0.007 b ]]> <![CDATA[-18.33±0.81 a ]]> SPI / D / ANs-2 <![CDATA[340.30±15.76 d ]]> <![CDATA[0.543±0.012 a ]]> <![CDATA[-19.67±0.32 a ]]> SPI / D / ANs-3 <![CDATA[354.17±24.90 d ]]> <![CDATA[0.436±0.015 c ]]> <![CDATA[-21.17±2.68 a ]]> SPI / D / ANs-4 <![CDATA[404.27±20.14 c ]]> <![CDATA[0.503±0.006 b ]]> <![CDATA[-22.07±1.43 a ]]> SPI / D / ANs-5 <![CDATA[440.80±8.78 b ]]> <![CDATA[0.543±0.006 a ]]> <![CDATA[-21.77±3.21 a ]]> SPI / D / ANs-6 <![CDATA[497.93±5.70 a ]]> <![CDATA[0.543±0.006 a ]]> <![CDATA[-22.60±1.45 a ]]> SPI / D / ANs-7 <![CDATA[517.30±13.17 a ]]> <![CDATA[0.507±0.006 b ]]> <![CDATA[-26.87±0.95 b ]]>

[0132] Different letters in the same column indicate that there are significant differences between the means of different samples (p<0.05).

[0133] As shown in Table 1, the average size of SPI / D / ANs nanoparticles increased with the increase in the number of cyclic reactions (p<0.05). The increase in the number of continuous reactions of ultrasound-assisted moist heat cycles corresponds to the increase in the degree of conjugation between SPI and dextran, indicating that ultrasound synergistically enhances the spatial effect of dextran. The larger the space occupied by dextran, the more obvious the cross-linking effect with the positively charged cross-linker ANs. In addition, the observed increase in particle size can be attributed to the interaction between protein and ANs and the bridging effect between ANs and dextran. The lower polydispersity index (PDI) indicates better dispersion stability of the nanoparticles. The PDI values ​​ranged from 0.43 to 0.53, indicating a wide particle size distribution and low monodispersity. This may be due to the fact that the addition of ANs may reduce the net surface charge of the nanoparticles, reduce electrostatic repulsion, and increase particle aggregation, thereby increasing the PDI value.

[0134] As shown in Table 1, the absolute value of the zeta potential increased from -21.17 mV to -26.87 mV as the number of cycles increased from 3 to 7. This increase indicates that the covalent grafting between SPI and dextran is more extensive, resulting in a higher degree of encapsulation of anthocyanins in the nanoparticles and a weakened surface shielding effect of the charge of the protein modifier. The addition of anthocyanins can also improve the stability of the SPI / D grafts, as the hydrophobic environment formed by SPI and dextran can protect anthocyanins from erosion by water molecules.

[0135] Experimental Example 5: Changes in the structure of nanoparticles after loading anthocyanins with SPI / D grafts

[0136] The nanoparticle samples were measured for UV-visible absorbance between 190 nm and 600 nm, and Fourier transform infrared spectroscopy and intrinsic fluorescence spectroscopy were performed on the nanoparticle samples using the method in Experimental Example 2. The nanoparticles were diluted to 0.1 mg / mL for synchronous fluorescence spectroscopy, and 5 mL aliquots were placed in a quartz cuvette with a path length of 1 cm for fluorescence analysis. Synchronous scanning was performed at Δλ of 15 nm and 60 nm, with a scanning speed of 1200 nm / min, a slit width of 2.5 nm, and a scanning range of 250 to 400 nm.

[0137] Fig.15 The results showed that as the number of cycles increased, the interaction between anthocyanins and SPI / D grafts increased and they were gradually encapsulated by the protein core. This encapsulation reduced the exposure of chromophores such as Trp and Tyr, thereby weakening the absorption. After the introduction of anthocyanins, the maximum absorption peak of SPI / D grafts was slightly blue-shifted, indicating the presence of a hypochromatic effect, confirming the interaction between SPI / D and ANs, which may be caused by changes in hydrogen bonds within the protein molecule.

[0138] Fig.16 It shows that after adding ANs, the amide A band peak of the nanoparticles increases from 3492 cm -1 Drift to 3482cm -1 This indicates that the hydrogen bonding interaction between SPI / D and ANs is strengthened. As the number of cycles increases, the transmittance decreases and the amide I peak increases from 1639 cm -1 Drift to 1631cm -1 , indicating that the structure has changed. The amide II peak has changed from 1543 cm -1 Move to 1527cm -1, indicating that the α-helix content is reduced and the disordered coil content may be increased. Compared with the SPI / D grafts, the addition of ANs leads to a general blue shift of the amide I band in SPI / D / ANs, indicating that the hydrogen bonding interaction between ANs and SPI / D is strengthened, leading to the change of secondary structure. In addition, the intensity of the amide II and III bands increases, indicating that SPI / D forms nanoparticles with ANs through hydrophobic and hydrogen bonding interactions.

[0139] Fig.17 It was shown that the addition of ANs and the increase in the number of ultrasonic-synergistic wet-heat cycles resulted in a gradual blue shift in the λmax of the nanoparticles, while the fluorescence intensity decreased significantly. This was due to the fact that polyphenols quenched the fluorescence of SPI / D through interactions such as rearrangement and energy transfer, which led to protein unfolding and exposure of Trp residues. The introduction of ANs also resulted in the appearance of a new peak specific to ANs around 320 nm, confirming the encapsulation effectiveness of ANs. Compared with SPI / D alone, the highest emission wavelength was red-shifted, which means that the microenvironment in the SPI / D / ANs nanoparticles is more polar, indicating that the hydrophobic interaction between ANs and SPI / D masks the hydrophobic domain of the protein.

[0140] Fig.18 and 19 It was shown that the fluorescence of Tyr and Trp would decrease with the increase of the cycle period, among which the quenching effect of Trp was more obvious, indicating that its interaction with ANs was stronger. The introduction of ANs also moved the absorption peak position of amino acids. At Δλ=15nm, the λmax of SPI remained basically unchanged, while at Δλ=60nm, there was an obvious blue shift, which indicated that the polarity of tyrosine changed very little, but the hydrophobicity of tryptophan increased and the polarity decreased, indicating that tryptophan was transferred to the non-polar cavity of the protein. The above results show that the interaction between SPI / D and ANs is more likely to occur near the tryptophan residue.

[0141] Experimental Example 6: Effect of SPI / D on the Retention and Stability of ANs

[0142] 1. Determination of ANs retention rate and stability

[0143] Oxidative stability (addition of hydrogen peroxide 0.5%, 1% and 1.5% (concentrations), oxidation at room temperature in the dark for 1 hour), metal ion stability (combination with 1 ml of 0.1 mol / L ferric chloride solution and storage in the dark for 6 hours), light stability (exposure to sunlight, ultraviolet light and darkness for 6 days), thermal stability (6 hours in a water bath at 60°C, 70°C, 80°C and 90°C), and storage stability evaluation for 6 days at 4°C. Samples were taken every 2 hours or every 2 days to determine the retention rate. The retention rate of ANs after 2 hours in simulated gastric digestive fluid and 5 hours in simulated intestinal digestive fluid was detected using the gastrointestinal simulated digestion stability test (the anthocyanin content in the SPI / D / ANs solution was determined using the pH difference method, and the retention rate of ANs was calculated accordingly. Retention rate (%) = C m / C 0 ×100(9), where C 0 represents the ANs concentration at time 0; C m represents the ANs concentration at m).

[0144] 2. Results

[0145] Thermal stability analysis

[0146] like Fig. 20 As shown in the figure, as the heat treatment temperature continued to increase, the ANs retention rate of SPI / D / ANs nanoparticles gradually decreased with different cycle numbers (p<0.05). However, at the same heat treatment time, the ANs retention rate in SPI / D / ANs nanoparticles was significantly higher than that of free ANs (p<0.05). After 6 hours of treatment at 90℃, the retention rate of SPI / D / ANs in different cycles ranged from 59.17% to 72.07%, with the highest retention rate in the seventh cycle. This suggests that the increase in the continuous reaction of ultrasound-assisted wet heat cycles enhances the steric hindrance of SPI with the dextran network, resulting in stronger hydrophobic and hydrogen bonding interactions with ANs. This tighter binding protects ANs from the solvent environment, thereby slowing down their degradation during heat treatment.

[0147] Storage stability analysis

[0148] Fig.21The results showed that, in a storage environment at 4°C, the retention rates of nanoparticles and free ANs did not change much with the extension of storage time, except for SPI / D / ANs-4 and SPI / D / ANs-5. Compared with ANs, the retention rate of nanoparticles increased significantly (except for SPI / D / ANs-1), and showed a pattern of first increasing, then decreasing, and finally increasing again in each cycle. SPI / D / ANs nanoparticles effectively retained ANs during storage, with the highest retention rate observed in the seventh cycle. This excellent performance was attributed to its dense internal network, which minimized the leakage of ANs during storage.

[0149] Photostability analysis

[0150] Fig. 22 It was shown that the retention rate of ANs decreased with the increase of exposure time to natural light, darkness and UV radiation. However, except for the 4th day under dark conditions, the retention rate of SPI / D / ANs nanoparticles was generally higher than that of free ANs, indicating that SPI / D can effectively protect ANs from degradation. It is worth noting that compared with dark conditions, the protection of ANs by SPI / D grafts under UV irradiation was more significant, with retention rates ranging from 51.71% to 89.28%, with the highest retention rate in the 7th cycle. SPI / D interacts with ANs through hydrogen bonds and hydrophobic interactions, with stronger binding and more stable encapsulation, which improves the protection of ANs and reduces degradation under light.

[0151] Oxidation stability analysis

[0152] like Fig.23 As shown in the figure, after being treated with hydrogen peroxide for 1 hour, the retention rates of all samples gradually decreased with the increase of hydrogen peroxide concentration (p<0.05). Compared with ANs, the retention rate of SPI / D / ANs nanoparticles showed an overall upward trend, among which, when the hydrogen peroxide concentration was 1.5%, the retention rate of SPI / D / ANs nanoparticles after 7 cycles was significantly improved.

[0153] Fe 3+ Ion stability analysis

[0154] Fig.24 It shows that after adding SPI / D, ANs are affected by Fe 3+ The effect of ions was small, and the effect was most obvious after 7 cycles (p<0.05). 3+The above results indicate that SPI can react competitively with metal ions, thereby reducing the effect of metal ions on ANs. In addition, the phenolic hydroxyl group of anthocyanin and the carboxyl group of SPI can also establish hydrogen bonds, thereby reducing the destructive effect of metal ions on ANs.

[0155] In vitro simulated digestion analysis

[0156] Fig.25 It was shown that the retention rate of SPI / D / ANs nanoparticles and ANs increased with the increase in the number of ultrasound-synergistic moist heat cycles, showing a situation of first rising, then falling, and then rising again. And the retention rate of SPI / D / ANs always exceeded the retention rate of ANs itself. In the intestinal digestion stage, the content of ANs decreased significantly compared with the gastric digestion stage, and the protective effect of SPI / D on ANs was particularly obvious after seven cycles (p<0.05). In the stomach, ANs will transform from the chalcone form to the more stable flavin cation form. The SPI / D used here effectively protected ANs during simulated gastric digestion. In contrast, the alkalinity of the intestinal environment is a key factor leading to the degradation of ANs and the reduction of bioavailability. During intestinal digestion, the protective effect will weaken as SPI decomposes.

[0157] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a high-performance soybean protein / glucan graft, characterized in that: The following steps are involved: (1) dissolving soy protein isolate and glucan in ultrapure water, adjusting the pH to neutral, and performing a preliminary reaction to obtain a mixed solution 1; (2) subjecting the mixed solution 1 to a low-temperature wet heat reaction and an ultrasound-assisted high-temperature wet heat reaction in sequence, and after multiple cycles, terminating the cycle reaction to obtain a mixed solution 2; (3) adjusting the pH of the mixed solution 2 to acidic, separating the solid and the liquid, and drying the supernatant to obtain a soy protein / glucan graft; The low temperature in the low-temperature wet heat reaction in step (2) is less than 65°C; the high temperature in the ultrasound-synergistic high-temperature wet heat reaction is greater than 80°C.

2. The preparation method according to claim 1, characterized in that: The final concentration of the soy protein isolate in ultrapure water in step (1) is 1.2-1.6% (w / v); The final concentration of the dextran in ultrapure water is 0.5-1.0% (w / v), and the molecular weight of the dextran is 35-45 KDa.

3. The preparation method according to claim 2, characterized in that: The conditions of the preliminary reaction in step (1) are 22-26° C. and stirring at 30-2000 rpm for 1.5-2.5 hours.

4. The preparation method according to claim 3, characterized in that: The low-temperature wet heat reaction in step (2) lasts for 10 to 30 minutes at a temperature of 55 to 65° C., and low-speed stirring is required at a speed of 5 to 120 rpm.

5. The preparation method according to claim 4, characterized in that: The ultrasound-assisted high-temperature wet heat reaction in step (2) is as follows: after the low-temperature wet heat reaction is completed, the temperature is raised to 80-90° C., and ultrasound-assisted reaction is used at the same time, the power of ultrasound is 200-500w, and the time is 5-30min; The number of the continuous cycles is 2 to 7 times.

6. The preparation method according to claim 5, characterized in that: The pH value after adjustment in step (3) is 4.0 to 5.0; The conditions for the solid-liquid separation are: 5000-10000 rpm, centrifugation for 20-30 min.

7. A soybean protein / glucan graft prepared by the preparation method according to any one of claims 1 to 6.

8. Use of the soybean protein / glucan graft according to claim 7 in stabilizing anthocyanins.

9. The use according to claim 8, characterized in that The method for stabilizing anthocyanins comprises: dissolving the soy protein / glucan graft and anthocyanin respectively with water to obtain a soy protein / glucan graft solution and anthocyanin solution, mixing them, and then homogenizing them at 5000-10000 rpm for 2-8 minutes to obtain a mixed solution 3, separating the solid from the liquid, taking the supernatant and drying it to obtain soy protein / glucan graft nanoparticles loaded with anthocyanin.

10. The use according to claim 9, characterized in that: The concentration of the soy protein / glucan graft in the soy protein / glucan graft solution is 5 to 10 mg / mL; The final concentration of anthocyanins in the anthocyanin solution is 5 to 10 mg / mL; The volume ratio of the soy protein / glucan graft solution to the anthocyanin solution is 1 to 2:1; The solid-liquid separation is performed under the conditions of 5000-10000 rpm and centrifugation for 5-20 min.